Potential Predictive Role of MicroRNAs in the Neoadjuvant Treatment of Esophageal Cancer - Vrana, David; Matzenauer, Marcel; Aujesky, Rene; Vrba, Radek; Neoral, Cestmir; Melichar, Bohuslav; Souček, Pavel (Anticancer research, 2017)
Esophageal cancer is a disease with disappointing prognosis. Currently, there are no predictive factors that can identify patients who on the one hand would likely benefit from tri-modality management and, on the other hand, would not be significantly affected by the morbidity accompanying the treatment. MicroRNAs are short non-coding RNAs responsible for post-transcriptional modification of gene expression by binding to 3'-UTR of messenger RNA and represent emerging potential predictive biomarkers of treatment (chemotherapy and radiotherapy) efficacy and toxicity. We reviewed the current literature, addressing the potential predictive role of microRNAs for efficacy of chemotherapy (specifically cisplatin, 5-fluorouracil, doxorubicin and paclitaxel) and radiotherapy, including predicted targets in the cell. Altogether 82 articles were identified and included in this review. This may be the first review on this topic specifically focusing on neoadjuvant treatment of esophageal cancer.
Keywords: prognóza; Predictive Value of Tests; adjuvantní chemoradioterapie; Prognosis; nádory jícnu; prediktivní hodnota testů; Humans; MicroRNAs; Neoadjuvant Therapy; lidé; Esophageal Neoplasms; Chemoradiotherapy, Adjuvant; mikro RNA; neoadjuvantní terapie